Effects of pressure work over a semi-infinite vertical oscillating cylinder - Palani, Govindasamy; Sarojini, A. (Zielona Góra: Uniwersytet Zielonogórski)
An arithmetical methodology is used to study natural convection with properties of pressure work over a semi-infinite vertical oscillating cylinder. The governing partial differential equations are set up and the resulting equations are changed into a non-dimensional form using the proper non-dimensional quantities.
Keywords: cylinder; finite difference; pressure work; oscillating; skin friction